The surprising wealth of pre-industrial England - Gregory Clark; Joe Cummins; Brock Smith (University of California, Department of Economics, 2010)
Occupations listed in wills reveal that as early as 1560 effectively only 60% of the English engaged in farming. Even by 1817, well into the Industrial Revolution, the equivalent primary share, once we count in food and raw material imports, was still 52%. By implication, incomes in pre-industrial England were close to those of 1800. Urbanization rates are not a good guide to pre-industrial income levels. Many rural workers were engaged in manufacturing, services and trade. The occupation shares also imply pre-industrial England was rich enough in 1560 to rank above the bottom fifth of countries in 2007.
Keywords: 330